(untitled) (Journal of Hama University, 2021)
The aim of the study was to investigate the contamination of drinking water used in poultry farms around Hama governorate, where 40 water samples were collected from each side of Hama with 10 samples from each area to study the physical (EC, Turbidity, hardness, pH, TDS), and chemicla (SO4, NO3, NO2, Cl, NH4) properties of water and, some agricultural pesticides (deltamethrin, diazinon, chlorpyrfos, malathion, carbendazim) and some heavy metals (Pb, Cd). The results showed an increase in the average physical values of conductivity, hardness and turbidity in the eastern and southeastern regions compared to the other regions. Also the same trend was taken by the sulfate, chloride and nitrate, which were of higher concentrations in the eastern and southeastern regions,while the pH values and the ammonium ion were similar in all regions. Concerning agricultural pesticides, traces of chlorpyrifos and deltamethrin were observed in west (50%) and north (20%) areas of Hama governorate, and no agricultural pesticide was recorded in the water of other regions. Also, with regard to heavy metal elements, all the values obtained were below the permissible limit, with the exception of only two samples, in which the lead concentration exceeded the permissible limit, and in eastern region.